2004
DOI: 10.1107/s090744490402181x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and atomic resolution X-ray diffraction of the catalytic domain of the large sialidase, nanI, fromClostridium perfringens

Abstract: Sialidases catalyse the removal of terminal sialic acids from a range of glycoproteins, glycolipids and oligosaccharides. They have been found in bacteria, viruses and parasites, where they play important roles in pathogenesis and/or microbial nutrition, and in mammalian cells, where they modulate cell-surface glycosylation associated with a range of cellular activities. Clostridium perfringens, a causative agent of gas gangrene and peritonitis in humans, possesses three sialidases: nanH, nanI and nanJ, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Structure Solution-A molecular replacement solution was readily obtained using CNS (34) with a pruned model of the sialidase from the leech (Macrobdella decora) (PDB code 1sll) as a search model (32). The leech sialidase shares 35% overall sequence identity with NanI and 37% identity within the catalytic domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure Solution-A molecular replacement solution was readily obtained using CNS (34) with a pruned model of the sialidase from the leech (Macrobdella decora) (PDB code 1sll) as a search model (32). The leech sialidase shares 35% overall sequence identity with NanI and 37% identity within the catalytic domain.…”
Section: Methodsmentioning
confidence: 99%
“…Data Collection-The 50-kDa catalytic domain (residues 243-694) of the C. perfringens NanI sialidase was subcloned, expressed, crystallized, and cryoprotected as described previously (32). All data were collected on station ID14-EH1 at the ESRF, Grenoble, France, at 100 K and at a wavelength of 0.934 Å. Diffraction data for the ligand free and Neu5Ac complex extended beyond 0.92 Å, but for considerations of completeness, data were limited to 0.97 Å ( A).…”
Section: Methodsmentioning
confidence: 99%
“…Although the 300 kDa sialidase described by Heuermann et al [22] might represent a multimer of the 72 kDa NanA protein, we did not detect such a protein on our immunoblots. The sialidase NanA of C. chauvoei is most closely related to the sialidase of C. septicum and to NanJ and NanI of C. perfringens (Figure 2), the structures of which have been studied in detail [8,10]. In this respect, it is interesting to note that C. chauvoei and C. septicum are phylogenetically very closely related [47] and at one time were classified phenotypically as the same species [48].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatically active site of sialidases is in the C-terminal end that contains the usual catalytic residues that are common to all sialidases [9-11], including a catalytic nucleophile tyrosine, an arginine triad that interacts with the carboxylate group of sialic acid, a tryptophan residue that forms a weak H-bond with the glycerol side chain of sialic acid, and an aspartic acid that forms H-bonds with the four OH-groups of sialic acid. Furthermore, the enzymatically active domain contains four "Asp-boxes" [10] characterized by the motif Ser-X-Asp-X-Gly-X-Thr-Trp, and the first arginine of the catalytic triad of sialidases generally belongs to a RIP (Arg-Ile-Pro) motif [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Coinciding with their highly conserved sialidase-like active site, it has been shown that trans-sialidases exhibit residual sialidase activity in the absence of the appropriate acceptor (Cross & Takle, 1993;Harrison et al, 2001;Gbem et al, 2013). In contrast to sialidases, it is interesting to note that the structural and mechanistic features of trans-sialidases remain understudied, as only a handful of these enzymes have been characterized (Cheng et al, 2008(Cheng et al, , 2009Gut et al, 2008;Newstead et al, 2004).…”
Section: Introductionmentioning
confidence: 99%